Fundamentals of engineering physics - Mukherjee, Moumita (Aryan Publishing House, 2011)
Fundamentals of engineering physics / Mukherjee, Moumita. -- Kolkata: Aryan Publishing House, 2011 530 M954 No. of Copies : 2